Multicultural Education Curriculum Development in Turkey - Aydin, Hasan (Mediterranean Journal of Social Sciences, 2012)
In recent years, Turkey has seen an increase in immigration and, consequently, also in the enrolment of internationalstudents. These students from many countries, with a variety of cultural, linguistic, ethnic, religious, and educational backgrounds are inneed of education that â€œteaches the value of cultural diversity.â€ Schools must also deal with issues related to differing socioeconomicbackgrounds, and, sometimes, limited awareness of diversity and a lack of cultural competence. Thus, it has become essential forTurkish schools to adopt a multicultural curriculum, restructured in accordance with knowledge of the right of all to education, in keepingwith principles of global justice. The purpose of this paper is to provide multicultural educators with such an insight from research ondevelopment curriculum of multicultural education. In addition, this paper offers ideas culled from successful multicultural programs in theU.S. and elsewhere and discusses how these ideas can be made useful in the Turkish system.